BIOM-58. ROLE OF CD79B Y196 MUTATION IN PCNSL AS A POTENT PREDICTIVE MARKER FOR FAVORABLE RESPONSE TO R-MPV TREATMENT AND DEVELOPMENT OF RAPID ALL-IN-ONE GENOTYPING SYSTEM FOR MOLECULAR MARKERS OF PCNSL. (14th November 2022) - Yamaguchi, Junya; Ohka, Fumiharu; Lushun, Chalise; Motomura, Kazuya; Aoki, Kosuke; Takeuchi, Kazuhito; Nagata, Yuichi; Ito, Satoshi; Mizutani, Nobuhiko; Ohno, Masasuke; Suzaki, Noriyuki; Takasu, Syuntaro; et al.
Abstract: Although high-dose methotrexate (HD-MTX)-based chemotherapy, such as rituximab, HD-MTX, procarbazine and vincristine (R-MPV) regimen, has significantly prolonged the survival of patients with primary central nervous system lymphoma (PCNSL), predictive factors for response to R-MPV have not yet been investigated. Then, we investigated the correlation of MYD88 L265P and CD79B Y196 mutations, which are the most frequently found molecular alterations in PCNSL, with prognosis of patients with PCNSL treated with R-MPV. 47 and 21 patients with PCNSL treated with R-MPV and HD-MTX respectively were included, and correlation of their MYD88 and CD79B status with prognosis was analyzed. R-MPV achieved an excellent tumor control rate (61.6% and 69.9% of 5-year progression-free and overall survival rates, respectively). Among the 47 patients, 36 harbored MYD88 L265P or CD79B Y196 mutations. While the MYD88 L265P mutation had no significant effect on survival, patients with CD79B Y196 mutations exhibited prolonged survival ( P < 0.05). However, the association of the CD79B Y196 mutation with a better prognosis was not observed in the HD-MTX cohort, which indicated that the CD79B Y196 mutation was a predictive marker for a favorable response to R-MPV. Furthermore, we established an all-in-one rapid genotyping system for these genetic mutations. This system enabled the detection of these genetic mutations in a small amount of biopsy samples within 90 min. In conclusion, we revealed that the CD79B Y196 mutation is associated with a good response to R-MPV, and the rapid and accurate genotyping system for MYD88 L265P and CD79B Y196 mutations that we developed in this study will enable reliable rapid molecular diagnosis and early prediction of response to R-MPV, which might help to determine the best treatment strategy for PCNSL.